2016
DOI: 10.21037/jtd.2016.07.74
|View full text |Cite
|
Sign up to set email alerts
|

Modified bronchial anastomosis in video-assisted thoracoscopic sleeve lobectomy: a report of 32 cases

Abstract: Background: Bronchial anastomosis is a key technical challenge in sleeve lobectomy, especially when using the video-assisted thoracoscopic surgery (VATS) approach. A retrospective study was conducted to evaluate the feasibility and safety of a modified bronchial anastomosis technique developed by the authors at Fujian Union Hospital.Methods: From October 2010 to October 2015, we performed 32 cases of VATS sleeve lobectomy through a three-port or single-port approach. All bronchial anastomoses were performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The first study describing video-assisted thoracoscopic (VATS) sleeve lobectomy was reported in 2002 [ 13 ]; after more than 10 years, there have been only a small number of case series reports [ 14 18 ], although the morbidity, mortality, and survival were comparable between VATS sleeve lobectomy and thoracotomy. The slow adoption of the thoracoscopic technique for sleeve resection is mainly due to the technical challenges involved in the bronchial anastomosis in VATS and its steep learning curve [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study describing video-assisted thoracoscopic (VATS) sleeve lobectomy was reported in 2002 [ 13 ]; after more than 10 years, there have been only a small number of case series reports [ 14 18 ], although the morbidity, mortality, and survival were comparable between VATS sleeve lobectomy and thoracotomy. The slow adoption of the thoracoscopic technique for sleeve resection is mainly due to the technical challenges involved in the bronchial anastomosis in VATS and its steep learning curve [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura and associates [ 27 ] reported an anastomosis with 16 stitches of interrupted sutures that required a long time because the thread was loosened or cut while ligating. In VATS sleeve lobectomy, Chen and colleagues reported a mean anastomosis time of 37.6 ± 12.0 min [ 18 ], and Wang and associates reported a median time of 44 (37–48) minutes for bronchial anastomosis [ 15 ]. The main features of our experience are the suture mode and segment bronchial sleeve resection without pulmonary resection.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (19) proposed an interesting modified anastomotic technique for VATS SL; in particular, we focused on a RM and right lower (RL) VATS SL performed by a uniportal approach.…”
Section: Right Medium (Rm) and Lower Vats Slmentioning
confidence: 99%
“…The Authors put one chest drainage through the operating port and a posterior venous catheter in the seventh or the eighth intercostal space. They documented a successful series of 32 VATS SL carried out by a threeportal (19) or a uniportal (5) approach without intraoperative deaths nor major complications due to surgery.…”
Section: Right Medium (Rm) and Lower Vats Slmentioning
confidence: 99%
See 1 more Smart Citation